Maxillary Sinus Cyst and Angiolipoma: A Case Report at Wangaya Regional General Hospital, Indonesia - Hamdani, Yovita; Pratama, I Nyoman Satria; Putra , Kadek Agus Suhardinatha (Pelopor Publikasi Akademika, 2025)
Paranasal sinus cysts are benign lesions that are often asymptomatic. In most cases, they are found in the maxillary sinus. Further radiological examinations, such as a head CT scan, are required. The diagnosis of angiolipoma is made through histopathological analysis. The purpose of this article is to establish the diagnosis and management of maxillary sinus cysts and angiolipoma. A 35-year-old male patient presented to the ENT clinic of Wangaya Regional General Hospital complaining of nasal congestion and headache. Based on anamnesis, physical examination, and supporting investigations in the form of a head CT scan, the patient was diagnosed with a maxillary sinus cyst and angiolipoma. The treatment chosen was surgery in the form of Functional Endoscopic Sinus Surgery (FESS) and Luc-Caldwell (LCW) procedures. After surgery, the complaints of nasal congestion and headache were reduced. Maxillary sinus cyst and angiolipoma can be challenging to diagnose because of their nonspecific clinical presentations. Initial diagnostic testing may include computed tomography (CT), and definitive diagnosis is made through histopathology. Treatment options include FESS and LCW.